A Research Update on Exendin-4 as a Novel Molecule Against Parkinson’s Disease - Singh, Niraj K.; Singh, Ashini; Varshney, Mini; Agrawal, Ritik (Current Molecular Medicine, 2023)
Parkinson's disease (PD) is the second most prevalent neurodegenerative disorder, and its consequences severely influence the quality of a patient's life and mobility. PD is characterized by bradykinesias with tremors and/or rigidity. Pathophysiologically, PD is associated with the gradual degeneration of dopaminergic neurons in the substantia nigra pars compacta of the midbrain, neuroinflammation, increased accumulation of the alpha (α)-synuclein, overburden of oxidative stress, and mitochondrial dysfunction. To date, there are no effective therapies with underlying shreds of evidence that alters the progression of PD. Exendin-4, a glucagon-like peptide 1 (GLP-1) receptor agonist, has gained attention for its tremendous neuroprotective potential against numerous neurodegenerative disorders, including PD. Further, several pieces of research evidence have suggested the beneficial role of Exendin-4 in PD-like experimental models. The present review article highlights the preclinical and clinical evidence of the therapeutic benefits of Exendin-4 against PD. Exendin-4 reverses the PD-like symptoms in experimental animals by dramatically minimizing the loss of dopaminergic neuronal and accumulation of α-synuclein in the PD-like brain. Further, it also reduces the mitochondrial toxicity and expression of pro-inflammatory mediators such as tumor necrosis factor (TNF)-α and interleukin (IL)-1β. These observations designate that Exendin-4 is a multifactorial compound that could be considered a safe, effective, and new ingredient for developing clinically useful pharmacotherapy for managing PD-like manifestations.
Keywords: Exendin-4